2018
DOI: 10.1186/s13568-018-0652-x
|View full text |Cite|
|
Sign up to set email alerts
|

Changes in feeding habits promoted the differentiation of the composition and function of gut microbiotas between domestic dogs (Canis lupus familiaris) and gray wolves (Canis lupus)

Abstract: Wolves (Canis lupus) and their domesticated and close relatives, dogs (Canis lupus familiaris), have great differences in their diets and living environments. To the best of our knowledge, the fundamental question of how the abundance and function of the gut microbiota of domestic dogs evolved to adapt to the changes in host feeding habits has yet to be addressed. In this study, our comparative analyses of gut metagenomes showed that the abundance of gut microbiota between the two species have some significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 66 publications
3
42
0
1
Order By: Relevance
“…Wu et al [176] found 15 bacterial species that differed in abundance between captive wolves and dogs. Furthermore, a metagenomic analysis of wolf and dog gut microbiotas revealed differences in microbial species and genes related to starch and cellulose digestion [177]. Lyu et al [177] suggested that the gut flora of dogs reflects adaptation to a diet of human food, most notably the presence of starch combined with a low intake of animal protein.…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al [176] found 15 bacterial species that differed in abundance between captive wolves and dogs. Furthermore, a metagenomic analysis of wolf and dog gut microbiotas revealed differences in microbial species and genes related to starch and cellulose digestion [177]. Lyu et al [177] suggested that the gut flora of dogs reflects adaptation to a diet of human food, most notably the presence of starch combined with a low intake of animal protein.…”
Section: Discussionmentioning
confidence: 99%
“…3 show the separation observed between the gut bacteria composition of group ML and group TL. Lyu 32 yielded differences in the ability to adapt to a captive environment. The difference in the ability to adapt to a captive environment may result from the different gut bacterial composition of red deer and fallow deer.…”
Section: Discussionmentioning
confidence: 99%
“…Another bacterium known to produce butyrate from protein sources is Fusobacterium varium (31), which was more abundant in a group of dogs fed meat-based raw diets for at least 1 year, suggesting an adaptation of the microbiome to the long-term diet (24). In addition, members of the Fusobacteriaceae family have been found to be more abundant in other carnivore species [cats: (18,32), wolves: (33,34), other carnivora: (17,35)], and dogs fed raw diets (19,23,36).…”
Section: The Effect Of Dietmentioning
confidence: 99%